The Role of Teachers’ Teaching Performance in Bolangitang Barat Elementary School : Competency, Motivation, and Teacher-Training Education - Nina Lamatenggo; Ansar Ansar; Arwildayanto Arwildayanto; Warni Sumar (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study aims to quantitatively measure the influence of teacher competence, teacher work motivation and training education (Training) on teacher performance. This research is included in the descriptive quantitative research. Partial Least Square (PLS) is the method used to analyze the data in this investigation. This research was conducted at a state elementary school in Bolangitang Barat. This study used a purposive sampling strategy, with participants drawn from elementary school Bolangitang Barat. The findings of this research suggest that factors such as education and training, competence, and teacher motivation in elementary school Bolangitang Barat, this leads us to the conclusion that to improve school teacher performance, it is necessary to provide education and training activities and also provide programs with the aim of increasing teacher competence. In addition, the teacher himself needs to have high motivation with the hope of help improve his performance.